Influence of additives on the purity of tetragonal phase and grain size of ceria-stabilized tetragonal zirconia polycrystals (Ce-TZP). Issue 1 (January 2019) - Zang, Sitian; He, Ningxiang; Sun, Xiaoting; Sun, Mingyue; Wu, Weiwei; Yang, Huazhe
Abstract: A comprehensive study on the influence of typical additives on zirconia (ZrO2 ) crystallization was presented. Zirconium nitrate pentahydrate (Zr(NO3 )4 ·5H2 O) and cerium(III) nitrate hexahydrate (Ce(NO3 )3 ·6H2 O) were employed as reagents, ethylenediaminetetraacetic acid disodium salt (EDTA-2Na) or glycerol were adopted as additives, and ammonia water was adopted as pH regulator. The ZrO2 powders were prepared by hydrothermal method. The crystal phase purity, grain size and micro morphology of the ZrO2 powders were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM) equipped with energy dispersive spectrometer (EDS) to investigate the influence of EDTA-2Na, glycerol and Ce 4+ content on the purity of tetragonal phase and the grain size of ceria-stabilized tetragonal zirconia polycrystals (Ce-TZP). It was found that EDTA-2Na could decrease the purity of tetragonal phase and alter the grain size of Ce-TZP nonlinearly, while glycerol could not decrease the purity of tetragonal phase and the grain size of Ce-TZP, and the grain size was not linear with the amount of glycerol; Doping Ce 4+ could increase the purity of tetragonal phase of zirconia but could not decrease the grain size, and the grain size was not linear with the Ce 4+ content; In addition, it was indicated that EDTA-2Na and glycerol could not improve the distribution uniformity of Ce 4+ . This study is expected to have provided a novel path to achieve tailored ZrO2 crystals with reduced low-temperature degradation.